Pengaruh Resiko Kredit Dan Kebijakan Deviden Terhadap Return On Assets Pada Sektor Perbankan Yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2022 - Intan, Amelisa Nurul; Suherman, Acep; Himawan, Irfan Sophan (As-Syirkah: Islamic Economic & Financial Journal, 2024)
This study aims to explain and examine the effect of Credit Risk on Return on Assets (ROA) in banking companies listed on the Indonesia Stock Exchange in 2020-2022, to examine the effect of Dividend Policy on Return on Assets (ROA) in banking companies listed on the Indonesia Stock Exchange in 2020-2022, to examine the interaction between Credit Risk and Dividend Policy in influencing Return on Assets (ROA) in banking companies listed on the Indonesia Stock Exchange in 2020-2022. The research method used in this research is descriptive and associative research with a quantitative approach. The location of this research is in banking sector companies listed on the Indonesia Stock Exchange (IDX) by analyzing financial statements using quantitative methods. The data used are financial reports from the official IDX website for 2020-2022. The population used in this study are companies in the banking sector listed on the IDX in 2020-2022. The sample in this study was 36 financial statement data for the period 2020-2022. The data collection technique in this research is literature study and documentation. In this study, the data analysis technique used was the classic assumption test and hypothesis testing using SPSS software. The results showed that there is a positive and significant influence between credit risk on return on assets, there is no influence between dividend policy on return on assets, and there is a positive and significant influence between credit risk and dividend policy on return on assets.